The associations between problematic smartphone use and blood pressure among 2,573 aged 9–17 years students in Shanghai, China - Liu, Shaojie; Lan, Yukun; He, Gengsheng; Chen, Bo; Jia, Yingnan (Frontiers in Public Health, 2022)
Objectives This study aimed to (1) examine the cross-sectional association between problematic smartphone use (PSU) and blood pressure (BP) in children and adolescents and (2) determine whether the association between PSU and BP differs by the grade of students. Methods We recruited a total of 2,573 participants from 14 schools in Shanghai by a two-stage sampling method. We derived BP data from the participant's most recent medical examination data, including systolic blood pressure (SBP) and diastolic blood pressure (DBP). We measured PSU by a modified PSU Classification Scale. We also assessed demographic characteristics, body mass index, behavioral variables, and physiological characteristics. Results High school students had higher BP and PSU scores than primary and middle school students. PSU on the dimension of information collection was associated positively with both SBP and DBP among primary and middle school students, with the β (95% CI) values of 0.282 (0.018, 0.546) and 0.229 (0.031, 0.427). Meanwhile, the dimension of the relationship of social network was associated positively with SBP among primary and middle school students, with a β (95% CI) value of 0.390 (0.062, 0.717). PSU on the dimension of information collection was positively associated with the development of high BP, with a OR (95% CI) value of 1.072 (1.011, 1.137) among primary and middle school students. Conclusions PSU might be a potential correlate of high BP among school-age children and adolescents. The associations between PSU and BP differed by the grade of students as well as according to the four dimensions of PSU.